Roy, D., Baker, W., & Hamilton, A. (2019). Teaching the arts: Early childhood and primary education (3rd ed.). Cambridge, England: Cambridge University Press. (Journal of Applied Learning and Teaching, 2019)
The collective wisdom has always been that in Early Childhood, the best way to engage and help a child learn is through physical play and movement. If such play and movement are structured as they are in the Arts, even better. Friedrich Froebel, who coined the word kindergarten (literally ‘infant garden’) in 1840, considered arts and crafts essential to stimulate the child’s imagination and develop physical and motor skills. By stating right at the start that babies learn through and with the Arts, the authors establish the central role of Arts in human life and learning.Authors David Roy, William Baker and Amy Hamilton focus on a topic that has been discussed in the education domain for several decades now, namely Arts Education in Early Childhood and Primary years. However, the role of early childhood and primary educators in Arts education is far more complex than you may at first expect. Moreover, any emphasis on ‘fun’ can also make a topic seem less serious but, in the field of Arts education, having fun becomes fundamental to achieving desired learning outcomes.